(untitled) (Vietnam Journal of Community Medicine, 2022)
Aim: Describe the learning style of students at Hanoi Medical University in 2022; Describe some factors affecting the learning style of students at Hanoi Medical University in 2022. Subjects and methods: A cross-sectional descriptive study on students from the first to the sixth year of Hanoi Medical University. Results: Among 330 students, 57.6% had unimodal PCOS (of which 24.6% was visual, 21.5% was auditory and 11.5% was motor) . In terms of multimodal PCH (42.4%), the combination of vision and hearing accounts for the highest proportion (13.9%). In the student’s personality, both introverted and extroverted personalities (43.3%) prevailed. Students with good academic performance have 3.74 times higher rate of multimodal problem solving (95% CI: 1.28-10.91) than the group with good academic performance. This number in the weak group is 6.06 times (95%CI: 1.22-29.99). There is a strong correlation between personality and the choice of more or less learning styles. The introvert-only personality has a higher ratio of multimodal learning styles than the extrovert-only group, ranging from 0.32-0.98 with p=0.041. Conclusion: Students with single-modal learning style account for a higher percentage than multimodality. Correlation was found between learning style and personality, learning style and academic scores.